Coilin is rapidly recruited to UVA-induced DNA lesions and γ-radiation affects localized movement of Cajal bodies - Bártová, Eva; Foltánková, Veronika; Legartová, Soňa; Sehnalová, Petra; Sorokin, Dmitry V; Suchánková, Jana; Kozubek, Stanislav (Nucleus, 2014)
Cajal bodies are important nuclear structures containing proteins that preferentially regulate RNA-related metabolism. We investigated the cell-type specific nuclear distribution of Cajal bodies and the level of coilin, a protein of Cajal bodies, in non-irradiated and irradiated human tumor cell lines and embryonic stem (ES) cells. Cajal bodies were localized in different nuclear compartments, including DAPI-poor regions, in the proximity of chromocenters, and adjacent to nucleoli. The number of Cajal bodies per nucleus was cell cycle-dependent, with higher numbers occurring during G2 phase. Human ES cells contained a high coilin level in the nucleoplasm, but coilin-positive Cajal bodies were also identified in nuclei of mouse and human ES cells. Coilin, but not SMN, recognized UVA-induced DNA lesions, which was cell cycle-independent. Treatment with γ-radiation reduced the localized movement of Cajal bodies in many cell types and GFP-coilin fluorescence recovery after photobleaching was very fast in nucleoplasm in comparison with GFP-coilin recovery in DNA lesions. By contrast, nucleolus-localized coilin displayed very slow fluorescence recovery after photobleaching, which indicates very slow rates of protein diffusion, especially in nucleoli of mouse ES cells.
Keywords: Cajalova tělíska; ultrafialové záření; buněčné linie; lidé; Green Fluorescent Proteins; G2 fáze; HeLa Cells; Cell Nucleus; Cell Line, Tumor; záření gama; Cell Line; buněčné jádro; Coiled Bodies; Gamma Rays; zelené fluorescenční proteiny; Recombinant Fusion Proteins; DNA; myši; Humans; buňky K562; Mice; Ultraviolet Rays; G2 Phase; rekombinantní fúzní proteiny; jaderné proteiny; zvířata; HeLa buňky; Animals; nádorové buněčné linie; K562 Cells; Nuclear Proteins